Effects of droplets in the air on light transmission in target optical detection. (May 2020) - Zhang, Chuanxin; Li, Tianjiao; Yuan, Yuan; Wang, Fuqiang; Tan, Heping
Highlights: The energy distribution model of the receiving surface affected by droplets in the air is established. The Monte Carlo ray tracing method is used to calculate the transmission of light in a single droplet. Droplets in the air have a similar convex lens effect on the parallel rays. The number of droplets affects the energy distribution of the receiving surface. Abstract: Rays hit droplets in the transmission path on severe weather conditions such as rain and fog during the target optical detection process. The presence of droplets causes the directions of rays and the amount of energy to change after rays pass through droplets, leading energy that eventually enters the detector to change, affecting target detection. This study establishes an energy distribution model of the receiving surface affected by droplets in the air based on the basic principle of light radiation transmission. The results of single and planar droplets in the air on the transmission of light are calculated by the Monte Carlo ray tracing method combining the physical properties of droplets and air. The effects of different distances between the droplets and receiving surface on the energy distribution of the receiving surface are analyzed. Droplets in the air have a similar effect on the parallel light with convex lens. The energy distribution is related to the distance between the receiving surface and droplets in the air. The energy recorded on the receiving surface and affected by droplets first converges to a point and then diverges. There are almost no rays corresponding to the droplets on the receiving surface when the distance between the receiving surface and droplets is sufficiently large. This study provides new ideas and methods for obtaining the influence of droplets in the air on the energy distribution of the receiving surface in target optical detection, which provides an effective reference for detection.